Pengembangan Media Pembelajaran Sistem Rem Hidrolik Sepeda Motor Untuk Meningkatkan Minat Belajar Mahasiswa Pendidikan Teknik Otomotif Universitas Muhammadiyah Purworejo - Bagus Adi Pratama; Suyitno Suyitno; Aci Primartadi (Pusat riset dan Inovasi Nasional, 2026)
This study aims to develop learning media for motorcycle hydraulic brake systems through three main aspects. First, it examines the development procedures covering the planning, design, and implementation stages. Second, it evaluates the feasibility of the developed media for Automotive Engineering Education students at Muhammadiyah University of Purworejo in terms of effectiveness, ease of use, content relevance, and visual and functional appeal. Third, the study analyzes the effect of the media on improving students’ learning motivation, including learning interest, active participation, and persistence in understanding automotive materials. The research employed a Research and Development (R&D) approach involving purposively selected students from the Automotive Engineering Education program. Data were collected using questionnaires to assess media feasibility and student responses. Data analysis consisted of a normality test, homogeneity test, and a t-test to identify significant differences between pre- and post-intervention learning outcomes. The results indicate that the developed learning media is feasible and effective, and has a positive impact on students’ learning motivation and learning outcomes at Muhammadiyah University of Purworejo.